1991
DOI: 10.1111/j.1469-8137.1991.tb00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural tolerance of cyanobacteria to the herbicide glyphosate

Abstract: SUMMARYSynechocystis PCC 6803 and Anabaena variabilis ATCC 29413 showed a high degree of tolerance to the herbicide glyphosate, applied as the free acid, the monoisopropylamine sait or the commercial formulation (Roundup''). Differential toxicity between herbicide formulations was observed (Roundup > isopropylamine salt > free acid) and correlated with their rates of uptake. There was no evidence of glyphosate degradation. Shikimate accumulation, together with partial alleviation of inhibition by aromatic amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…In the same way, the Cyanobacteria, which are photosynthetic prokaryotes, exhibited a wide range of EC 50 values varying from 2 to 1183 mg/L. However, despite this variability in EC 50 values, Cyanobacteria in general appear to be less sensitive to glyphosate than eukaryotic photosynthetic microorganisms (Powell et al, 1991). This tolerance of glyphosate could be explained by various mechanisms, notably the ability of Cyanobacteria to metabolize phosphonate (Forlani et al, 2008).…”
Section: Impact Of Glyphosate On Aquatic Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, the Cyanobacteria, which are photosynthetic prokaryotes, exhibited a wide range of EC 50 values varying from 2 to 1183 mg/L. However, despite this variability in EC 50 values, Cyanobacteria in general appear to be less sensitive to glyphosate than eukaryotic photosynthetic microorganisms (Powell et al, 1991). This tolerance of glyphosate could be explained by various mechanisms, notably the ability of Cyanobacteria to metabolize phosphonate (Forlani et al, 2008).…”
Section: Impact Of Glyphosate On Aquatic Microorganismsmentioning
confidence: 99%
“…With the exception of Roundup, in which the surfactant is known to be polyethyloxylated tallowamine (POEA), information about the surfactants involved are generally not clearly stated by the manufacturers. Furthermore, several studies have shown that the surfactant molecules also make the commercial product (in particular, Roundup) more toxic than the technical grade compound (salt or free acid forms) (Powell et al, 1991;Diamond & Durkin, 1997;Giesy et al, 2000;Tsui & Chu, 2003).…”
Section: Formulationmentioning
confidence: 99%
“…O-X, the herbicide also inhibited nitrogenase activity by about 50% but the dry matter increased. Powell et al (1991) reported that nitrogenase activity was more sensitive to the isopropylamine salt of glyphosate than was photosynthetic O 2 evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that the shellfish were contaminated with BMAA, but also remarked that there was intensive chemical-based agriculture in the region [77]. Interestingly, cyanobacteria have been found to be remarkably resistant to glyphosate [78,79], and this could contribute to the recent record-setting algal blooms in the Great Lakes region, where glyphosate is extensively used on genetically modified (GM) RoundupReady crops [80].…”
Section: Bmaa and Als In Guammentioning
confidence: 99%